Arrangement Investment-Based Insurance with Sharia Principles Post Enactment Law of Number 40 Year 2014 Concerning Insurance - Wetria Fauzi (AHKAM : Jurnal Ilmu Syariah, 2018)
Indonesia's legal system comes from civil law brought by the Dutch royal government to Indonesia during the colonial period. Civil law can be traced its roots to French civil law to Roman law. Insurance is equated with gambling The concept of insurance in insurance legislation states that insurance is a risk transfer institution. Despite the Law No. 40 of 2014 on Insurance, the law is still conceptualize insurance as an institution of protection. This new insurance law is a dual insurance system, which regulates conventional and sharia insurance systems. It needs to be initiated The Formation of Special Law regulates sharia insurance in Indonesia, because conventional and sharia are two very different things in principle.